Acral lentiginous melanoma: A retrospective study. (9th October 2020) - Redi, Ugo; Marruzzo, Giovanni; Lovero, Stefano; Khokhar, Hassan Tahir; Lo Torto, Federico; Ribuffo, Diego
Abstract: Background: Acral lentiginous melanoma (ALM) carries one of the worst prognoses among other subtypes. This malignant tumor is found on the distal limbs and is usually detected at late stages. Hereby, the authors present their experience on this melanoma subtype. Methods: A retrospective study was conducted. Data were extracted from patients' medical records and from phone interviews. Results: A total of 43 patients were included in the study. The main signs and symptoms disclosed by the patients were bleeding (41.9%), size greater than 6 mm (41.9%), change in size (37.2%), change in shape (30.2%), rise above the surface of the skin (27.9%), change in color (20.9%), irregular borders (16.3%), and inflammation (16.3%). The first healthcare professional consulted was a general practitioner or a dermatologist in the majority of cases (88.3%). Only 44.2% of the patients were sent by their first physician for a biopsy, whereas 30.3% were sent by the 2nd physician. 14 patients underwent biopsy within 1 month from the first appointment with a physician, while 20 patients within 3 months and 9 patients within 6 months. Only 7 patients sought medical attention in the first 3 months; 21 patients sought medical care between 3 months and one year from the appearance of the lesion, while the remaining 15 patients waited more than a year. Conclusions: One of the major issues found in ALM is represented by the diagnostic delay; this may be due to either the patients or the physicians' failure to recognize warning signs.